2021
DOI: 10.3390/su131810277
|View full text |Cite
|
Sign up to set email alerts
|

Cybernetics Approach Using Agent-Based Modeling in the Process of Evacuating Educational Institutions in Case of Disasters

Abstract: In the context of an emergency, evacuating people from a location in the shortest possible time is essential, as is the high degree of safety that people should expect when evacuating. Lately, in Romania there have been more and more fire events generated by different causes. This article will use agent-based modeling to simulate an emergency evacuation model in NetLogo. The model has been used to perform and analyze various scenarios. With the help of NetLogo, we managed to perform 400 simulations with the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…In case of fire, the smoke and fire spread present a vertical characteristic with a fast speed, which will increase the difficulty of safe evacuation, and due to the influence of many factors such as no smoke prevention and power failure, elevators will also be stopped. Therefore, it is of great significance to conduct research on personnel evacuation in public places in the field of public security [ 60 ]. However, the previous studies of scholars on the evacuation of public places mainly focus on performance-based fire prevention design, escape path planning based on an algorithm model, the influence of fire smoke spread law on personnel evacuation, and the changes of psychological characteristics and behavior of personnel during evacuation.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…In case of fire, the smoke and fire spread present a vertical characteristic with a fast speed, which will increase the difficulty of safe evacuation, and due to the influence of many factors such as no smoke prevention and power failure, elevators will also be stopped. Therefore, it is of great significance to conduct research on personnel evacuation in public places in the field of public security [ 60 ]. However, the previous studies of scholars on the evacuation of public places mainly focus on performance-based fire prevention design, escape path planning based on an algorithm model, the influence of fire smoke spread law on personnel evacuation, and the changes of psychological characteristics and behavior of personnel during evacuation.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Researchers from different majors have studied human behavior and the effectual factors on public emergency evacuation behavior. Some scholars believe that not only the imminent impacts of the disaster perceived by people could affect their behavior, but the built environment features also have considerable effects on the occupants' evacuation behavior [11,12]. Studies generally revealed that human behavior during an emergency varies based on risk perception [11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars believe that not only the imminent impacts of the disaster perceived by people could affect their behavior, but the built environment features also have considerable effects on the occupants' evacuation behavior [11,12]. Studies generally revealed that human behavior during an emergency varies based on risk perception [11,13]. People's risk perception can be affected by many factors, including individual characteristics and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Raphael mentioned that human behavior during a disaster depends on “ preexisting social grouping and, level of perceived physical threat or damage, attachment to the family ” ( Raphael, 2005 ). Experience and the results of pivotal studies revealed that human behavior during an emergency varies based on risk perception ( Xenidis and Kaltsidi, 2022 ; Ștefan Ionescu et al, 2021 ). People's risk perception can be affected by many factors, including individual characteristics and environmental factors ( Verdière et al, 2015 ; Bahmani et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al explored the impact of public knowledge on disaster avoidance before, during, and after the disaster ( Wu et al, 2022 ), showing that the residents' disaster knowledge can positively affect their evacuation choice. Studies in the field of earthquake risk perception and preparedness manifested socio-demographic characteristics of residents such as age, education, borning place, and disaster experience and loss have significant impacts on earthquake preparedness ( Ao et al, 2020 ; Ao et al, 2021 ) Considering the environmental impact on people's behavior during an emergency, the built environment features considerably affect the occupants' evacuation behavior ( Ștefan Ionescu et al, 2021 ; Ao and Martek, 2020 ).…”
Section: Introductionmentioning
confidence: 99%